GELAS KAYU BIDARA LAUT (GEYU BILUT) SEBAGAI ANTIMALARIA - Najiyyah, Siti Ulfatun; Ardiansyah, Ardiansyah; Prayitno, Oktavianus; Safitri, Rinitha Dinda; Megantari Ekaputri, Ni Putu Galuh (Program Kreativitas Mahasiswa - Penelitian, 2014)
Malaria until now still remain one of the main problem of world health. About 40% or 2.4 billion people in the world live in malaria endemic areas. Therefore, malaria cases in Indonesia on 2008 is about 1.624.930 cases. More than 25% province in Indonesia shows resistence to sulfadoksin-pirimetamin, cloroquin and kina in the last decade. People ofÂ  NTB believes that stewed water of geyu bilut works as antimalaria. The purpose of this research is to know the effectivity of stewed water of geyu bilut as antimalaria. The research that had been done is an experimental research using post test only control group design. The research sample are 30 Balb/c mice that have fullfiled inclusion criteria and have been selected by using simple random sampling. Every sample was infected with 200ÂµL P.berghei intraper-itoneally on day 0. Treatment start given with sondage 2-4 hours after infection, the treatment are 0.3ml aquades to negative control group, 0.3ml cloroquin with dose 5 mg/kgBW to positive control group and 0.3ml of stewed water of geyu bilut with concentration 0,0003% to the treatment group, the dose start given with orally once per day, from day 0 to day 7. The thin blood smear was made on day 1 to 8 and was checked by using light microscope with total magnify 1000x, percentage of parasitemia was counted per 1000 erythrocytes. Primary data that has been collected then processed using Kruskal Wallis Test. The result that was collected from stewed water of geyu bilut with dose based on empiric fact has parasitemia percentage that donât have significant difference with negative control and positive control group (p>0,05). Therefore, from this research we can conclude that 0,3ml stewed water of geyu bilut with concentraion 0.0003% is not effective as antimalaria.Â Keywords: malaria, parasitemia percentage, geyuÂ  bilut, Strychnos ligustrina BI.